Experiências do laboratório de realidade virtual da PUCRS - Duarte, Lúcio Mauro (2001)
This work presents the efforts of the Computer Science School at PUCRS to implant the Virtual Reality Laboratory(LRV). With the support of the Pró-Reitoria de Pesquisa(Office of Research), of the Foundation of Support to Research in Rio Grande do Sul(FAPERGS), and of the National Council of Research(CNPq) we began in 1996 the implantation of the Virtual Reality Laboratory of PUCRS. This initiative is pioneer in our state and the second initiative in this area in the country. We are developing research to apply virtual reality in the areas of Education, Architecture, Robotics and Human-Computer Interfaces. To support this development we are still working in the implementation of tools and drivers to control virtual reality devices as gloves, helmets, trackers and force-feedback devices. All material developed until now is available in the Internet through the Computer Science School’s site at http://www.inf.pucrs.br/~grv. This site has been used by several other institutions as an information source.